Kerja Sama Indonesia-Interpol dalam Menangani Isu Penyelundupan Narkoba di Wilayah Perbatasan Indonesia - Sara Gabriella (Intermestic: Journal of International Studies, 2019)
This article aims to analyze Interpol’s efforts of drug trafficking eradication in Indonesia within cooperation framework. Employing tracing method, the study applied International Regime concept in elaborating the existing regime’s role in shaping Indonesia’s effort in handling drug trafficking cases. This study contributes to the academic discourse of international regime theory by focusing on Krasner’s concept of three main variables of regime, i.e. national interest (egoistic self-interest), political power, as well as norms and principles. The result shows that cooperation under regime framework helps shape and influence Indonesia’s consistent manner of addressing drug trafficking cases in more organized way. This serves as an effort to strengthen cooperation between Indonesia and Interpol, considering that the nature of drug trafficking as a transnational crime issue that goes beyond nation’s border and demands intergovernmental cooperation.